Terapi Zikir Jama’ati di Desa Luwoo dan Tenggela Kabupaten Gorontalo - Aris Saefulloh (Al-Ulum, 2012)
Jama’ati Muslim group of Luwoo and Tenggela villages in Gorontalo regency is one of the groups that routinely remembrance activities in their environment. By using psychological, this paper will attempt to explore the existence and the implementation of remembrance "Jama'ati" performed occasionally in which the congregation can help in reducing symptoms of anxiety psychosis, so the remembrance that there has been a therapeutic means for the congregation whom face depressive problem . Recitation (zikir) is done routinely will greatly assist in the process of forming the character of their souls. Recitation is one way to obtain spiritual concentration. For those who follow this zikir routinely can implement it in a variety of methods.